A Window in South Anne Street, 1983 - O’Donnell, Mary (ABEI Journal, 2021)
“A Window in South Anne Street, 1983” by Mary O’Donnell. Written for “Eavan Boland — In Her Many Images”, ABEI Journal 23.2 (2021).